Controlling of Ru/Cu Removal Rate Selectivity during CMP by Using Ammonium Sulfate and Inhibitor. (1st January 2019) - Wang, Ziyan; Zhou, Jianwei; Wang, Chenwei; Zhang, Jiajie; Wang, Qinwei; Zhang, Xue; Wang, Chao
Abstract : The controlling of Ru/Cu removal selectivity during the ruthenium-based barrier chemically mechanical polishing (CMP) plays a vital role in controlling the dishing and erosion of the patterned wafer. In this paper, the removal selectivity of Ru to Cu was mainly studied in H2 O2 -based slurry using ammonium sulfate as a complexing agent and 2, 2'-[[(methyl-1H-benzotriazol-1-yl)methyl]imino]diethanol (TT) as an inhibitor. Polishing results indicate that the Ru/Cu removal selectivity can be adjusted from 0.1 to 2.7 by adjusting the concentration of TT or ammonium sulfate in the slurry. The inhibition mechanism of TT was studied in detail by means of electrochemistry and X-Ray photoelectron spectroscopy (XPS). The results show that TT can reduce the corrosion rate and removal rate of Cu by adsorption passivation;on the contrary, TT did not have a significant impact on Ru. In addition, the dishing and erosion of the ruthenium-based pattern wafer were further tested, showing that the slurry having a removal selectivity of barrier (Ru and Ta) to Cu greater than 1.0 can effectively correct the dishing and erosion.